2012
DOI: 10.1128/aem.06416-11
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of a Dehalococcoides-Containing Microbial Consortium Reveals Prophage Activation

Abstract: Chlorinated solvents are among the most prevalent groundwater contaminants in the industrialized world. Biodegradation with Dehalococcoides-containing mixed cultures is an effective remediation technology. To elucidate transcribed genes in a Dehalococcoides-containing mixed culture, a shotgun metagenome microarray was created and used to investigate gene transcription during vinyl chloride (VC) dechlorination and during starvation (no chlorinated compounds) by a microbial enrichment culture called KB-1. In bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…A previous study revealed that a number of phage-related genes in Dhc195 are significantly upregulated when the growth phase transits from late exponential phase to early stationary phase (33). Similarly, a D. mccartyi phage was induced in the dechlorinating KB-1 culture when TCE was omitted (50). This suggests that the phage-related genes in D. mccartyi might be induced under environmental stress.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study revealed that a number of phage-related genes in Dhc195 are significantly upregulated when the growth phase transits from late exponential phase to early stationary phase (33). Similarly, a D. mccartyi phage was induced in the dechlorinating KB-1 culture when TCE was omitted (50). This suggests that the phage-related genes in D. mccartyi might be induced under environmental stress.…”
Section: Discussionmentioning
confidence: 88%
“…Early transcriptional studies had detected genes encoding BvcA and VcrA in KB-1 cultures dechlorinating TCE, cis-DCE, VC, and 1,2-DCA and had also found that BvcA gene transcripts were more abundant with the substrate cDCE (17). Subsequent microarray data that found genes for VcrA most highly transcribed in KB-1 cultures in general, with vcrA being the only RDase gene transcribed in KB-1 cultures grown on VC (41). These microarray data also revealed transcription of the Geobacter RDase gene in a TCE-in- duced KB-1 culture (41).…”
Section: Resultsmentioning
confidence: 99%
“…The KB-1 metagenome (Joint Genome Institute IMG Taxon Object ID 2013843002), including all known curated KB-1 dehalogenase sequences from multiple studies (6,21,41) (final database of 40,772 entries) was used as a sequence database to compare to mass spectra. All MS/MS samples were analyzed using Mascot (version 2.3.02; Matrix Science, London, United Kingdom).…”
Section: Methodsmentioning
confidence: 99%
“…Low cellular yields in the Dehalococcoidetes and Dehalobacter, oxygen sensitivity of RDases, and failure to produce functional heterologous RDases to date are key hurdles to purification and characterization of an RDase's substrate range. In addition, even when fed a single substrate Dehalococcoides strains have been shown to express multiple RDases simultaneously -further confounding purification of individual RDases from OHRB cultures [47,48,56]. Recent work with heterologous expression of PceA from D. restrictus [49 ] employed removal of the twin arginine ('RR') leader sequence, and addition of two fusions before cloning (streptavidin, to help with recovery, and PceT trigger factor).…”
Section: Rdase Diversitymentioning
confidence: 99%